Synergism of the Bacillus thuringiensis Cry1, Cry2, and Vip3 Proteins in Spodoptera frugiperda Control - Soares Figueiredo, Camila [UNESP]; Nunes Lemes, Ana Rita [UNESP]; Sebastião, Isis [UNESP]; Desidério, Janete Apparecida [UNESP] (Springer Nature, 2019)
The polyphagous caterpillar, Spodoptera frugiperda, has been controlled with either chemical insecticides or transgenic plants such as Bt maize that expresses the cry and/or vip genes of the Bacillus thuringiensis (Bt) bacterium. Despite the efficiency of Bt toxins in lepidopteran control, populations resistant to Bt plants have emerged in different locations around the world. Thus, understanding how combined proteins interact against pests can assist resistance control and management. This work demonstrated the toxicity of Cry1Ab, Cry1Ac, Cry1Ca, Cry1Ea, Cry2Aa, Cry2Ab, Vip3Aa, and Vip3Ca in single and combined assays against S. frugiperda neonatal larvae. All protein mixtures had synergistic action in the control of the larvae. The Vip3Aa + Cry1Ab mixture had the highest toxicity, sequentially followed by Vip3Aa + Cry2Ab, Cry1Ab + Cry2Ab + Vip3Aa, Cry1Ea + Cry1Ca, Cry1Ab + Cry2Ab, Vip3Ca + Cry1Ea, and Vip3Ca + Cry1Ca. Cry1Ab, Cry1Ac, Cry2Ab, and Vip3Aa bound to more than one site on the brush border membrane vesicles (BBMV) of S. frugiperda. The Cry1Ab and Cry1Ac proteins share binding site, while Cry1Ab does not share binding site with the Cry2Aa and Cry2Ab proteins. The Vip3Aa protein does not share receptors with the tested Cry1 and Cry2. The results suggest that combination these tested proteins may increase toxicity against S. frugiperda neonates.
Keywords: Competition assays; Cry proteins; Fall armyworm; Vip3 proteins